Syntheses of some constituents of zingiber cassumunar - Pittaya Tuntiwachwuttikul (2018)
Syntheses of the aromatic compounds cis-3-(2′, 4′, 5′-trimethoxyphenyl)-4-[(E)-2‴, 4‴, 5‴-trimethoxy-styryl]cyclohex-l-ene (1), cis-3-(3′, 4′-dimethoxyphenyl-4-[(E)-3‴, 4‴-dimethoxystyryl] cyclohex-1-ene (2), cis-3-(3′, 4′-dimethoxyphenyl)-4-[(E)-2‴, 4‴, 5‴-trimethoxystyryl]cyclohex-1-ene (3), (E)-4-(3′, 4′-dimethoxyphenyl)but-3-en-1-ol (5), and (E)-4-(3′, 4′-dimethoxyphenyl)but-3-enyl acetate (6) have been carried out. © 1980 Australian Journal of Chemistry.